The Moral Psychological Justification of Anger: An Exploration of Self-Respect and Recognition - Jinjin Zhang; Zhiheng Xiong; Hao Zheng; Xiangzhen Ma (Behavioral Sciences)
In the field of moral psychology, traditional perspectives often evaluate anger based on its consequences, either validating or condemning it for its perceived benefits or harms. This paper argues for a shift in focus from the outcomes of anger to its moral and psychological foundations. By integrating insights from psychological research, this study posits that the fundamental nature of anger is intrinsically linked to the quest for recognition. Justified anger is defined as an emotional response to the unmet need for fair acknowledgment, while unjustified anger stems from feelings of superiority and the pursuit of higher status. This paper distinguishes between these two forms of anger, providing a more nuanced and intuitive understanding of the emotion. This interpretive framework not only aligns with our experiential understanding of anger but also offers a theoretical bridge to reconcile divergent philosophical and psychological perspectives. This study emphasizes the importance of addressing the underlying issues of recognition and self-esteem, suggesting that anger, when properly understood and managed, can serve as a constructive force for social justice and mutual respect.